The physical condition for the first time accepted the service of officers of internal affairs of Ukraine - Verenga Y.V; Prontenko K.V; Bondarenko V.V; Bezpaly S.M; Hutoryansky O.V (Kharkov National Pedagogical University, 2013)
The analysis of the level and dynamics of the physical condition and the adaptive capacity of the first accepted the service of police officers. The study involved 112 employees of the first medical-age group, which took initial training courses. The index of physical condition and the adaptive capacity of the cardiovascular system was analyzed. Found that the initial level of physical condition in 52.7% of employees is defined as the average. Adaptive capabilities of the majority of workers (76.8%) are characterized by stress adaptation mechanisms. Found non-significant deterioration in the value of the index of physical condition and the adaptive capacity of the first year of service. Proven lack of effectiveness of physical training of workers in the period of initial training. Found that one of the ways to improve the physical fitness of workers is to validate the content of physical training with regard to their physical condition and the posts to which they are assigned.